Control Device Engineering for Aquaponic Monitoring System - Siskandar, Ridwan; Kusumah, Billi Rifa (Indonesian Aquaculture Society (MAI), 2019)
Aquaponic cultivation systems require good care and management. Aquaponics that are not managed properly have great potential to cause failure in aquaponic cultivation itself. To simplify management, a system that can simplify the process is needed. The purpose of this research is to create a system that can help manage aquaponic cultivation. The system has a built-in aquaponic condition monitoring feature via an installed sensor. The conditions monitored by this system are conditions of air temperature, humidity, water temperature, light intensity, level of turbidity of water, and height of fish feed at the feedlot. The system has two automation features. The first automation feature is the automation of fish feeding with a certain time lag. The second automation feature is the automation of the water heater engine. Water heater engine will be turned on or off at a certain temperature. The system also features an engine control feature in aquaponics that includes a water pump engine, an aerator engine, and a water heater engine. System monitoring, automation and control features can be accessed by users via the web. Testing of the system has indicated that the system is functioning properly in accordance with the objectives. The algorithm is correct, so the system output matches the expected output.